An Empirical Approach to Studying Debris Flows - Implications for Planetary Modeling Studies. - BOURKE, MARY (My University, 2002)
High-resolution images acquired by the Mars Global Survey Mars Orbiter Camera show gullies on the walls of impact craters and valley systems on Mars. Depositional aprons associated with these gullies have been interpreted by Malin and Edgett [2000] to be characteristic of debris flow and to indicate the presence of sources of liquid water at shallow depths below the Martian surface. By focusing on a terrestrial debris flow we test the application of Chezy-type modeling to provide more direct estimates of the dynamics of proposed debris flows on Mars. Traditionally, planetary scientists, constrained by available remotely sensed data, have used a range of flow models to gain insights from deposits into the behavior and rheologic nature of features such as lava flows, debris flows, and gravity-driven flows. On the basis of these model results, broad interpretations of the physics governing flows of granular materials have been tempting based on limited field-derived data. This study tests and validates the extent to which the absolute value and relative variations of empirical parameters derived from the Chezy-type models describe the behavior of the General?s slide debris flow (38.24 N, 78.23 W) in Madison County, Virginia. The results indicate that extreme caution must be taken when interpreting model results for turbulent flows of granular materials. We obtained high-precision topographic profiles, superelevation data, sedimentary facies, and sedimentary textural properties over the debris flow. This study focuses on the empirical parameter C , whose value gauges energy dissipation in a flow, thereby called flow resistance. Using field observations, both variations and absolute values of C along the debris flow have been computed using two approaches: (1) assuming constant volumetric flow rate Q , where only topography and high-resolution images are required to compute channel dimensions, and (2) a variable Q , calculated using field derived data. Assuming near-Newtonian flow conditions in the debris flow, estimated values of C range from 0.035 to 0.099. When Q is fixed, C decreases as a function of distance downstream. When Q varies and C is computed from field-derived flow speeds, its value tends to increase downstream slightly. These opposite results have been compared to the field observations to determine which best describes the behavior of the flow. The variations in C downstream, obtained using the flow speeds, are most consistent with the geomorphic evidence for erosion of material by the debris flow and the presence of bends in the channel. The average values of C , 0.036?0.33 for the General?s slide, have been compared with computed C values for Newtonian and near-Newtonian flows to assess the rheology of the flow during emplacement. Our terrestrial study demonstrates that advances in understanding of the dynamics of debris flows on the Mars depends on obtaining debris flow speeds in addition to channel topography and flow thickness, rather than just on channel topography, flow thickness, and the assumption that Q is constant. Mars Orbiter Camera (MOC) and Mars Observer Laser Altimeter (MOLA) data can be used to derive channel topography, flow thickness, and possibly flow speeds. Such data will provide more direct estimates of the dynamics of debris flows on Mars than are currently available. I NDEX T ERMS : 5470 Planetology: Solid Surface Planets: Surface materials and properties; 5494 Planetology: Solid Surface Planets: Instruments and techniques; 6225 Planetology: Solar System Objects: Mars; 8040 Structural Geology: Remote sensing; 8194 Evolution of the Earth: Instruments and techniques
PUBLISHED
Keywords: Debris flow; Chezy; Modeling; Planetary; General's slide; Mars